1996
DOI: 10.1097/00006123-199607000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transient Moderate Hyperventilation on Dynamic Cerebral Autoregulation after Severe Head Injury

Abstract: These results confirm the finding that dynamic autoregulation is disturbed in severe head injury and that moderate transient hyperventilation can temporarily improve the efficiency of the autoregulatory response, probably as a result of a transient increase in vascular tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(46 citation statements)
references
References 40 publications
7
38
0
1
Order By: Relevance
“…We found that increased ambient PCO 2 levels were associated with increased odds of autoregulatory failure in the early postoperative period. Previous studies in experimental models and in adult humans have shown similar effects of PCO 2 on CPA (35)(36)(37)(38)(39)(40). Because PCO 2 is vasoactive in the pulmonary vasculature, changes in PCO 2 are used in certain circumstances to adjust pulmonary vascular resistance in infants after cardiac surgery.…”
Section: Postoperative Cerebral Autoregulationmentioning
confidence: 83%
“…We found that increased ambient PCO 2 levels were associated with increased odds of autoregulatory failure in the early postoperative period. Previous studies in experimental models and in adult humans have shown similar effects of PCO 2 on CPA (35)(36)(37)(38)(39)(40). Because PCO 2 is vasoactive in the pulmonary vasculature, changes in PCO 2 are used in certain circumstances to adjust pulmonary vascular resistance in infants after cardiac surgery.…”
Section: Postoperative Cerebral Autoregulationmentioning
confidence: 83%
“…Decreasing the PCO 2 values from a baseline of 37 to 28 mm Hg results in an improvement in the dynamic ARI. 38 The mechanism of improvement in autoregulation induced by hyperventilation is not clear. Possible mechanisms to account for this improvement may include an improved CPP, alterations in the pH value of the CSF, and increased vascular tone.…”
Section: Hyperventilationmentioning
confidence: 99%
“…38 If an improvement in autoregulation is the result of enhanced vascular tone induced by hypocapnia, then this improvement can be lost if the vascular tone returns to baseline. Moreover, a recent prospective randomized trial of chronic hyperventilation for 5 days in severely head-injured patients did not show a benefit from this treatment.…”
Section: Hyperventilationmentioning
confidence: 99%
“…9,[11][12][13]15 In Tiecks' original publication, 9 it is implied that a least-squares method was used to find the best fit in each case. The drawback with this approach is that it depends on another model parameter, namely, the critical closing pressure, that Tiecks et al assumed to be fixed at 12 mm Hg.…”
Section: Years)mentioning
confidence: 99%
“…Clinical applications of the thigh cuff technique have included patients with orthostatic hypotension, 10 carotid artery disease, 11 head injury, [12][13][14] and studies of the effects of anesthetic agents on cerebral autoregulation. 15,16 Despite its increasing use in cerebrovascular research, several aspects of the thigh cuff method have not been described.…”
mentioning
confidence: 99%